History of Benzodiazepine Prescriptions and Risk of Dementia: Possible Bias Due to Prevalent Users and Covariate Measurement Timing in a Nested Case-Control Study - Richardson, Kathryn; Mattishent, Katharina; Loke, Yoon K; Steel, Nicholas; Fox, Chris; Grossi, Carlota M; Bennett, Kathleen; Maidment, Ian; Boustani, Malaz; Matthews, Fiona E; Myint, Phyo K; Campbell, Noll L; et al. (American journal of epidemiology, 2019)
Previous estimates of whether long-term exposure to benzodiazepines increases dementia risk are conflicting and are compromised by the difficulty of controlling for confounders and by reverse causation. We investigated how estimates for the association between benzodiazepine use and later dementia incidence varied based on study design choices, using a case-control study nested within the United Kingdom’s Clinical Practice Research Datalink. A total of 40,770 dementia cases diagnosed between April 2006 and July 2015 were matched on age, sex, available data history, and deprivation to 283,933 control subjects. Benzodiazepines and Z-drug prescriptions were ascertained in a drug-exposure period 4–20 years before dementia diagnosis. Estimates varied with the inclusion of new or prevalent users, with the timing of covariate ascertainment, and with varying time between exposure and outcome. There was no association between any new prescription of benzodiazepines and dementia (adjusted odds ratio (OR) = 1.03, 95% confidence interval (CI): 1.00, 1.07), whereas an inverse association was observed among prevalent users (adjusted OR = 0.91, 95% CI: 0.87, 0.95), although this was likely induced by unintentional adjustment for colliders. By considering the choice of confounders and timing of exposure and covariate measurement, our findings overall are consistent with no causal effect of benzodiazepines or Z-drugs on dementia incidence.